1998
DOI: 10.1046/j.1469-8137.1998.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of arbuscular and ectomycorrhizal Eucalyptus coccifera: growth response, phosphorus uptake efficiency and external hyphal production

Abstract: Eucalyptus coccifera Hook., a plant capable of forming both arbuscular mycorrhizas and ectomycorrhizas, was used to compare the effects of the two mycorrhizal types on phosphorus uptake and C allocation. Seedlings were grown in a P-deficient soil\sand mixture inoculated with peat\vermiculite spawn of Laccaria bicolor (Maire) Orton or Thelephora terrestris (Ehrh.) Fr. ; or with 250-µm sievings from leek colonized by Glomus caledonium (Nicol. & Gerd.) Trappe & Gerde., Glomus sp. type E3 or Glomus mosseae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
2
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 52 publications
6
98
2
1
Order By: Relevance
“…The percentage of the total root length colonized by the AM fungus was determined using the gridline intersect technique (Giovannetti and Mosse, 1980). The length of the extraradical mycelium in soil was determined by a modified and combined method according to Jones et al (1998) and Newman (1966). The specific absorption rate (SAR) was defined as the amount of nutrients absorbed per unit of root mass and was calculated as follows: SAR = Plant nutrient uptake (µg)/Root mass (mg) (Azcón et al, 2003).…”
Section: Harvest and Chemical Analysismentioning
confidence: 99%
“…The percentage of the total root length colonized by the AM fungus was determined using the gridline intersect technique (Giovannetti and Mosse, 1980). The length of the extraradical mycelium in soil was determined by a modified and combined method according to Jones et al (1998) and Newman (1966). The specific absorption rate (SAR) was defined as the amount of nutrients absorbed per unit of root mass and was calculated as follows: SAR = Plant nutrient uptake (µg)/Root mass (mg) (Azcón et al, 2003).…”
Section: Harvest and Chemical Analysismentioning
confidence: 99%
“…Glasshouse experiments comparing the benefits provided to eucalypts by ECM and VAM associations have shown a greater benefit from ECM (Jones et al, 1998). Inoculation with VAM fungi alone substantially promoted the growth of eucalypts in some cases (Lapeyrie & Chilvers, 1985 ;Jasper & Davy, 1993), but not in others (Adjoud et al, 1996).…”
mentioning
confidence: 99%
“…Other data showed that the activity of extraradical mycelium ranged from 0 to 32% in hyphae extracted from soil, greatly increasing in hyphae attached to colonized roots: 96% in 6-, 9-and 13-week-old G. mosseae and G. intraradices hyphae (Sylvia 1988). Other authors reported that the length of vital extraradical hyphae ranged from 20 to 40 m m −1 colonized root in Eucalyptus coccifera seedlings inoculated with three different AM fungi (Jones et al 1998). Our recent data are comparable with the previous values, since SDH-positive hyphae ranged from 22 to 74 m m −1 colonized root length in G. mosseae.…”
Section: Visualization Of Intact Mycorrhizal Network Spreading From mentioning
confidence: 94%
“…Many studies, carried out after destructive extraction from the soil, have reported that the length of extraradical AM mycelium ranged from 2.6 to 54 m/g soil and from 1.6 to 1,420 cm/cm root (Tisdall and Oades 1979;Abbott and Robson 1985;Jakobsen et al 1992;Dodd et al 2000). Non-destructive investigations of AM extraradical mycelium, performed in root observation chambers and in vitro systems, yielded only qualitative data on its structure and growth before and after the establishment of the symbiosis (Friese and Allen 1991;Bago et al 1998a;Jones et al 1998). The first visualization of intact AM mycelium extending from mycorrhizal roots into the extraradical environment was obtained by means of a bidimensional model system which utilized two Millipore membranes "sandwiched" around the roots of individuals' plantlets.…”
Section: Visualization Of Intact Mycorrhizal Network Spreading From mentioning
confidence: 99%